Pengaturan Perdagangan Jasa Intemasional Dalam GATSAVTO - sefriani sefriani (Fakultas Hukum Universitas Islam Indonesia, 2005)
The implementation of liberalization principle periodically is determined by flexibility. The liberalization process must be conducted with respect to national interest and the level ofdevelopment ofits nations both for individual sectors andentire sector.lt is expected that the objective of the GATS is to create trade liberalization of services. To achieve the objective, itis needed to understand the services provider to fully comprehend GATS regulation. Without understanding GATS rules, it will be difficult for the regulator and service providers to compete directly with foreign supplier service which flooded the Indonesia market.